Policy Statement on Clinical Informatics Fellowships and the Future of Informatics-Driven Medicine - Kannry, Joseph; Smith, Jeff; Mohan, Vishnu; Levy, Bruce; Finnell, John; Lehmann, Christoph U.; on behalf of the Clinical Informatics Program Directors Group-AMIA (Applied Clinical Informatics, 2020)
Board certified clinical informaticians provide expertise in leveraging health IT (HIT) and health data for patient care and quality improvement. Clinical Informatics experts possess the requisite skills and competencies to make systems-level improvements in care delivery using HIT, workflow and data analytics, knowledge acquisition, clinical decision support, data visualization, and related informatics tools. However, these physicians lack structured and sustained funding because they have no billing codes. The sustainability and growth of this new and promising medical subspecialty is threatened by outdated and inconsistent funding models that fail to support the education and professional growth of clinical informaticians. The Clinical Informatics Program Directors' Community is calling upon the Centers for Medicare and Medicaid Services to consider novel funding structures and programs through its Innovation Center for Clinical Informatics Fellowship training. Only through structural and sustained funding for Clinical Informatics fellows will be able to fully develop the potential of electronic health records to improve the quality, safety, and cost of clinical care.
Keywords: clinical informatics; professional training; education; Accreditation Council on Graduate Medical Education; Centers for Medicare and Medicaid Services; education and strategies for HIT